Adsorção de polieletrólitos em superfícies opostamente carregadas - Silva, Alexandre Nogueira da [UNESP] (2015)
Understanding the interactions between polyelectrolytes and oppositely charged macroíons is important due to the great number of biological processes and technological advances in which they are related. In this context the process known as adsorption is quite important, which led to a series of theoretical, experimental and theoretical-computational studies for his better understanding. On systems with plane geometry the problem has analytical solution, however for spherical and cylindrical geometry this no longer occurs due to the problem of lack of analytical solutions for the electrostatic potential in these geometries. The experiments show that there is a scaling relation between the concentration of ionic species contained in the electrolytic solution in which the polyelectrolyte-macroíon system lies and the surface charge density of the polymer and macroíon. In this study we used the concept of factorization, stemmed on the Supersymmetric Quantum Mechanics, applied to Edwards equation to obtain an approximate analytic solution for the spherical case in an agreement with the experimentally observed